The classroom actual teaching and learning process at biology bilingual program - Herman Resyadi; Nurfajriah Basri; Sri Rahayu Juniati; Muhammad Yani; Evi Sohriani (EKSPOSE, 2021)
The objectives of this research were to find out the actual teaching and learning process and to what extent the use of English at Biology Bilingual program. This research employed the descriptive study which involved a lecture and one class of Biology Bilingual Program as the subject of the research. The data were collected through observation and video recording then analyzed by Classroom Discourse Frame. This research revealed that the teaching and learning process used both English and Bahasa Indonesia. It also reported that Lesson Frame, Lesson Support Frame, and Commentary Frame were used at the classroom activity. The language alternation was dominated by the lecture to clarifying and explaining the material and the Bahasa Indonesia was rarely used in the classroom teaching and learning process.Tujuan penelitian ini adalah untuk mencari tahu proses belajar mengajar actual dan sejauh mana penggunaan bahasa Inggris pada Program Biologi Bilingual. Penelitian ini menggunakan metode deskriptif yang melibatkan dosen dan salah satu kelas di Program Biologi Bilingual sebagai subjek penelitian. Data dalam penelitian ini dikumpulkan melalui observasi dan rekaman video yang kemudian dianalisis dengan Classroom Discourse Frame. Penelitian ini menemukan bahwa proses belajar mengajar menggunakan bahasa Inggris dan Bahasa Indonesia. Lesson frame, Lesson Support Frame, dan Commentary Frame digunakan dalam aktivitas kelas. Pergantian bahasa juga didominasi oleh dosen untuk memberikan klarifikasi dan mengklarifikasi materi pembelajaran selain itu bahasa Indonesia jarang digunakan dalam kegiatan belajar mengajar.